(untitled) (Research, Society and Development, 2022)
The objective of this article is to understand and analyze the history of didactics and its concept evolution in the field of education. In its theoretical grounds, the concept of dialogue is a key element to its explanation and educational analysis. The method used is the historical documentary review, based on a hermeneutic track on intellectual production developed historically and socially. Interpreted data were organized under a logical and chronological order of the main representatives of didactics. The most outstanding ones as well as paradigms, models, elements, sequence and didactic environments together with the clear difference of the concept of curriculum led to the identification of four stages: pre-didactics, dialectic didactics, classic didactics and digital times didactic. One of the first definitions refers to didactics as the art in the method of teaching and learning. Afterwards, theoretical elaboration brought about the concepts of differential, general and specific didactics. Later, didactics started being considered as a science, recognizing that it makes part of pedagogy with a practical dimension and with scientific grounds. Currently, based on the contributions of neurosciences and of digital progress, a new discipline was created: Neurodidactics, which optimizes the brain development, together with dialogic didactics, which highlights the clue role of dialogue to foster learning. In conclusion, educators should recognize that didactics has undergone changes and must privilege dialogue as a principle in the reconceptualization of knowledge in the field of education.